A Quick Walkthrough untuk Pengenalan Teknologi IC - Aminuddin Rizal (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2019)
Technology brought by human race has been evolving from known stone age, axe age, wood age and until we now reach the point where semiconductor or integrated circuit (IC) technology support human life. Its implicitly important to us to know, how current technology developed and what possible next technology look like. In this paper, we emphasize the quick walkthrough how our scientist and practical engineer made IC. Furthermore, a cheat sheet provided for a very basic equation we use when we made IC. Experiment on this research performed by using open source software which allow others to redo the same experiment. The outcome of this paper is well-structured introduction about IC technology and global discussion regarding next generation technology.